Antimicrobial Proteins and Peptides in Early Life: Ontogeny and Translational Opportunities - Battersby, Anna J.; Khara, Jasmeet; Wright, Victoria J.; Levy, Ofer; Kampmann, Beate (Frontiers in Immunology, 2016)
Whilst developing adaptive immune responses, young infants are especially vulnerable to serious infections including sepsis, meningitis and pneumonia. Antimicrobial proteins and peptides (APPs) are key effectors that function as broad-spectrum anti-infectives. This review seeks to summarise the clinically relevant functional qualities of APPs and the increasing clinical trial evidence for their use to combat serious infections in infancy. Levels of APPs are relatively low in early life, especially in infants born preterm or with low birth weight (LBW). There are several rationales for the potential clinical utility of APPs in the prevention and treatment of infections in infants: (a) APPs may be most helpful in those with reduced levels; (b) during sepsis microbial products signal via pattern recognition receptors (PRRs) causing potentially harmful inflammation which APPs may counteract; and (c) in the era of antibiotic resistance, development of new anti-infective strategies is essential. Evidence supports the potential clinical utility of exogenous APPs to reduce infection-related morbidity in infancy. Further studies should characterize the ontogeny of antimicrobial activity in mucosal and systemic compartments, and examine the efficacy of exogenous-APP formulations to inform translational development of APPs for infant groups.